Identification of cervical epidural space: A comparison study between contrast spread and loss of resistance techniques - Perper, Yakov (Frontiers in Pain Research, 2022)
Background and objectives Early epidural space identification is critical to the efficacy and safety of cervical epidural steroid injections (CESI). Currently, the accepted method for epidural space recognition is the loss of resistance technique (LORT). I hypothesized that the contrast spread technique might recognize epidural space concurrently with or sooner than LORT and that smaller needles might be employed with the fluoroscopy only method but not with LORT. To test my hypotheses, I conducted a comparison study. Methods The study participants were patients from my practice with a clinical diagnosis of cervical radiculitis divided into two groups of 20 each, who underwent CESI with either an 18 G or a 25 G Tuohy needle. All CESIs were performed utilizing the fluoroscopy only method. Then, LOR was tested using an Epidrum device that was observed for 30 s; if the Epidrum deflated, the result was positive. Results LOR was positive in 12 out of 20 patients in the 18 G group and 2 out of 20 in the 25 G group. The 95% confidence interval test for proportion revealed a statistically significantly lower rate for epidural space detection by LORT in both groups: [0.385, 0.815] in the 18 G and [-0.031, 0.231] in the 25 G group. Statistical significance of the difference between groups in LOR accuracy rate (60% vs. 10%) was confirmed by z-test for independent proportions: z = 3.31 (p < 0.001), Cohen's h = 1.13. Conclusion Fluoroscopy only method might be a safer alternative to LORT as it employs a different concept, might recognize epidural space sooner, and favors smaller needles. Clinical trial registration NCT05260294.